PENINGKATAN LAYANAN INSTANSI PENDIDIKAN MENGGUNAKAN BACKUP DATA DALAM UPAYA MEMPERMUDAH AKSES INFORMASI - Martanto Martanto (Teknik Informatika, 2019)
Data is a very important need for an Education institute, one of them is SMK Persatuan Ummat Islam. Because data is an important asset that must be protected and protected by its security. For this reason, a media is needed that can store data that are important and valuable assets so that they are guaranteed security and maintenance. Data processing is connected to the local area network (LAN) of SMK Persatuan Ummat Islam. Storage media with good and reliable performance will certainly greatly assist agencies for data storage in improving information access services at educational institutions. It is very important to secure data from the server so that it is necessary to backup the data by adding software or hardware as a backup server computer. To be guaranteed the data backup process periodically requires an application that can backup data automatically from the server or client. NAS4Free is a server with a Linux-based operating system that is very specialized to handle data storage centrally, so that it becomes one of the very good solutions to be implemented, because by using one media as a center of data storage can reduce the risk of data loss or data damage. And can restore (restore) data if the computer is damaged. So that the hope can facilitate the work of educators and education staff in improving services in educational institutions using data backup in ensuring the security and maintenance of data which are important and valuable assets